Analisis Pelaksanaan Program Pelibatan Keluarga dan Masyarakat pada Penyelenggaraan Pendidikan di Taman Kanak-Kanak - Adiman Adiman; Naufalia Nuraya; Endang Sri Budi Herawati; Rusi Rusmiati Aliyyah (Alignment:Journal of Administration and Educational Management, 2021)
This study aims to describe the implementation of family involvement program policies in the implementation of education at Pembina Sumber Kindergarten, Cirebon Regency. The research method used is a qualitative method with a case study model to analyze the implementation of the program according to the criteria. Data collection techniques used in-depth interviews (depth interviews) and questionnaires which were first tested for validity with content validity techniques by experts (expert judgment). Data analysis was carried out by following the Miles and Hubberman model. The results showed that the implementation of the family and community involvement program in the implementation of education at the Pembina Sumber Kindergarten was carried out according to technical instructions. From the various planned programs, it is necessary to optimize the provision of library facilities in the form of a reading corner for parents. Empowerment of parents/guardians in inspiration classes as motivators/inspirers for students needs to be optimized. In conclusion, the family involvement program in the implementation of education at the Sumber Pembina Kindergarten is carried out according to Permendikbud No. 30 years 2017. Keywords: Implementation, Children's Education, Involvement of Parents